The prevalence of occupational stress as a non-auditory effect of noise among palm oil mill workers in 7 sections of two selected mills - Roya Latifi Naeini,; Mohd Tamrin, Shamsul Bahri (Scienceline Publication, 2014)
Palm Oil Mills are among the nosiest industrial workplaces, whereby excessive noise poses a threat to the health of organization and cause serious consequences. Excessive noise exposure gradually affects auditory and non-auditory aspects of health. The set symptoms are referred to as occupational stress, having a direct impact on concentration, thereby reducing the efficiency and productivity levels of organization. Therefore the objective of this study was to determine and the prevalence of occupational stress among Oil Palm Mill Workers in seven sections of two selected mills The study’s scope was on the non-auditory effects of excessive noise while . The participants were 62 workers of two selected Palm Oil mills. They were chosen through proportional stratified sampling. Based on the objective of this study the environmental sound levels were measured in seven different section while on the other hand O’Donnell inventory was utilized as a tool to determine the stress level. Evidence shows that Physiological and performance effects are the two most important body reflexes affected by high exposure risky noise levels. Noise as an occupational factor contributes to high occupational stress levels